RT-PCR Protocols Second Edition - King, Nicola.; King, Nicola. (Methods in Molecular Biology,, 2010)
Once a tedious, highly skilled operation, reverse-transcription polymerase chain reaction (RT-PCR) has become a routine and invaluable technique used in most laboratories. In RT-PCR Protocols, Second Edition, expert researchers fully update the technologies presented in the popular previous edition, such as competitive RT-PCR, nested RT-PCR, RT-PCR from single cells, and RT-PCR for cloning. In addition, newer technologies are also explored, including multiplex RT-PCR, RT-LATE-PCR, and the greatly advanced field of real-time quantitative RT-PCR, while recent advances in creating the optimum RT-PCR reaction, e.g. RNA extraction, primer design, and reverse transcription, end the book with their indispensable input. Written in the highly successful Methods in Molecular Biology™ series format, chapters include brief introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes sections, highlighting tips on troubleshooting and avoiding known pitfalls. User friendly and up-to-date, RT-PCR Protocols, Second Edition acts as a handy companion to scientists from numerous diverse backgrounds who wish to explore further the marvels of gene expression.